Gallant by Bold: final year degree online exhibition bachelor of Graphic Design class of 2021: graphic design / Fakulti Seni Lukis & Seni Reka UiTM Shah Alam - Universiti Teknologi MARA, Fakulti Seni Lukis & Seni Reka (Fakulti Seni Lukis & Seni Reka UiTM Shah Alam, 2021)
Graphic design is the art or profession of visual communication that combines images, words, and ideas to convey information to an audience, especially to produce a specific effect.